Studi Tentang Peran Notaris Dalam Masyarakat Dan Kepentingan Umum - Munawarah Pratiwi, Windi Ramadhani, Andri Nurwandri, Eka Putri Wiedya Andynie, Muhammad Iqbal, (Jurnal Pusat Studi Pendidikan Rakyat, 2023)
Notaries are public officials who have an important role in various aspects of law and public life. refer to UUJN Number. 2 Year 2012 article 1 states that a notary is a public official who is authorized to make authentic deeds and other authorities The presence of a public accountant is reasonable with legal guidelines that aim to assist and serve individuals who require valid written evidence and provide legal witnesses to various agreements, transactions, and other legal acts. In order for the work and obligations of public accountants to run well, legal officers are expected to agree on a set of general or moral rules in their work and laws regarding the position of public accountants. This obligation is a consequence that must be required of a person who carries out a lawful summons order, including a legal officer, in carrying out his obligation. Of course, this obligation is not only from an ethical point of view but also based on related regulations, in this case UUJN Number. 2 Year 2014. The purpose of this study is to describe more broadly about how the role of notaries in society and their relationship with the public interest.